The homeostasis model assessment of insulin resistance is a judgment criterion for metformin pre-treatment before IVF/ICSI and embryo transfer cycles in patients with polycystic ovarian syndrome - Gao, Rui; Qin, Lang; Li, Zhengyu; Min, Wenjiao (Frontiers in Endocrinology, 2023)
Purpose: To explore the value of the homeostasis model assessment of IR (HOMA-IR) as a judgment criterion for metformin pre-treatment before in vitro fertilization/ intracellular sperm injection (IVF/ICSI) and embryo transfer (ET) for polycystic ovarian syndrome (PCOS) patients. Materials and methods: Clinical and laboratory information of PCOS patients who received IVF/ICSI-ET from January 2017 to September 2021 were retrospectively analyzed. We compared the clinical pregnancy rate (primary outcome) and controlled ovarian stimulation (COS) related parameters (secondary outcomes) between patients with and without metformin pre-treatment for all PCOS patients not grouped by HOMA-IR, PCOS patients with HOMA-IR < 2.71 and PCOS patients with HOMA-IR ≥ 2.71. Results: Nine hundred and sixty-nine PCOS patients who received GnRH-antagonist protocol were included in this study. For all PCOS patients, metformin group showed comparable clinical pregnancy rates in fresh ET cycles and frozen ET cycles compared with control group (55.9% vs. 57.1%, p=0.821 and 63.8% vs. 60.9%, p=0.497). For PCOS patients with HOMA-IR < 2.71, the clinical pregnancy rates in both fresh ET cycles and frozen ET cycles were statistical similar between two groups (61.5% vs. 57.6%, p=0.658 and 70.6% vs. 66.7%, p=0.535). For PCOS patients with HOMA-IR ≥ 2.71, the clinical pregnancy rate in fresh ET cycles were comparable between two groups (51.5% vs. 56.3, p=0.590), but it was statistical higher in metformin group than control group in frozen ET cycles (57.1% vs. 40.0%, p=0.023). The metformin group had less oocytes retrieved, lower cleaved oocyte rate, available D3 embryo rate, blastocyst formation rate and available blastocyst rate than control group. Conclusion: HOMA-IR is a judgment criterion for metformin pre-treatment before IVF/ICSI-ET in patients with PCOS. Metformin pre-treatment could be added for PCOS patients with HOMA-IR ≥ 2.71 during frozen IVF/ICSI-ET cycles to improve the clinical pregnancy rate.